2011
DOI: 10.1007/bf03404178
|View full text |Cite
|
Sign up to set email alerts
|

Active Transportation Environments Surrounding Canadian Schools

Abstract: Objectives: Walking or cycling to school represents an opportunity for children to engage in physical activity. The study objectives were to: 1) describe active transportation policies, programs, and built environments of Canadian schools and their surrounding neighbourhoods, and 2) document variations based on urban-rural location and school type (primary vs. secondary vs. mixed primary/secondary schools). Methods: 397 schools from across Canada were studied. A school administrator completed a questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…As observed in our study as well as by O'Loghlen et al, few primary and secondary schools promote active transport. O'Loghlen et al show that while most schools authorize students to use their bikes and offer bike racks (70%), less than half (40%) have a program to encourage active transport. Clearly, promotion of active transportation is an inexpensive intervention with demonstrated effectiveness .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As observed in our study as well as by O'Loghlen et al, few primary and secondary schools promote active transport. O'Loghlen et al show that while most schools authorize students to use their bikes and offer bike racks (70%), less than half (40%) have a program to encourage active transport. Clearly, promotion of active transportation is an inexpensive intervention with demonstrated effectiveness .…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, research demonstrates the importance of promoting PAS which develop students' motor skills for running, throwing, and jumping that can become part of lifelong active lifestyles without requiring engagement in regular team competition. 51 As observed in our study as well as by O'Loghlen et al, 52 few primary and secondary schools promote active transport. O'Loghlen et al 52 show that while most schools authorize students to use their bikes and offer bike racks (70%), less than half (40%) have a program to encourage active transport.…”
Section: Discussionsupporting
confidence: 74%
“…Accuracy of the Ruler Tool for the study area was assessed by measuring environmental features of known dimensions (e.g., professional sports fields); the correlation between the obtained measure and the known sizes was r = 1.00. Google Earth and the Ruler Tool have been used in other research when GIS data are not available, such as for measuring road widths (Pinkerton, Rosu, Janssen, & Pickett, 2013) or proportion roads with sidewalks (O’Loghlen, Pickett, & Janssen, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Studies in Australia, Canada, the USA and Europe have identified that children's active travel to school can increase daily levels of physical activity (Cooper et al, 2005;Schofield et al, 2005;Saksvig et al, 2007;Davison et al, 2008;McDonald, 2008;van Sluijs et al, 2009;Faulkner et al, 2009;Panter et al, 2010;Leslie et al, 2010;O'Loghlen et al, 2011) and may help children meet daily physical activity recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to this trend, childhood obesity has been recognised as a global epidemic (World Health Organisation (WHO), 2005a), with high prevalence in the USA, Europe and Ireland (WHO, 2005a, b;Evans et al, 2010). From a public health perspective increasing energy expenditure by facilitating daily active travel to school may help to combat the global rise in obesity and many of the related chronic health conditions (O'Loghlen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%